The impact of COVID-19 restrictions on participant enrollment in the PREPARE trial - David Pogorzelski; Paula McKay; Michael J. Weaver; Todd Jaeblon; Robert A. Hymes; Greg E. Gaski; Joanne Fraifogl; James S. Ahn; Sofia Bzovsky; Gerard Slobogean; Sheila Sprague; Gerard P. Slobogean; et al. (Contemporary Clinical Trials Communications, 2022)
Background: At the initiation of the COVID-19 pandemic, restrictions forced researchers to decide whether to continue their ongoing clinical trials. The PREPARE (Pragmatic Randomized Trial Evaluating Pre-Operative Alcohol Skin Solutions in Fractured Extremities) trial is a pragmatic cluster-randomized crossover trial in patients with open and closed fractures. PREPARE was enrolling over 200 participants per month at the initiation of the pandemic. We aim to describe how the COVID-19 research restrictions affected participant enrollment. Methods: The PREPARE protocol permitted telephone consent, however, sites were obtaining consent in-person. To continue enrollment after the initiation of the restrictions participating sites obtained ethics approval for telephone consent scripts and the waiver of a signature on the consent form. We recorded the number of sites that switched to telephone consent, paused enrollment, and the length of the pause. We used t-tests to compare the differences in monthly enrollment between July 2019 and November 2020. Results: All 19 sites quickly implement telephone consent. Fourteen out of nineteen (73.6%) sites paused enrollment due to COVID-19 restrictions. The median length of enrollment pause was 46.5 days (range, 7–121 days; interquartile range, 61 days). The months immediately following the implementation of restrictions had significantly lower enrollment. Conclusion: A pragmatic design allowed sites to quickly adapt their procedures for obtaining informed consent via telephone and allowed for minimal interruptions to enrollment during the pandemic.